Building Community Resilience through Adaptive Governance: An Institutional Approach in Gorontalo - Ahmad Zukri; Amna Amna; Dina Mauliana (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study aims to examine the role of adaptive governance in strengthening community resilience in Gorontalo, Indonesia, particularly in communities surrounding Lake Limboto that are vulnerable to environmental degradation, flooding, and socio-economic challenges. The study focuses on governance effectiveness, stakeholder participation, institutional responsiveness, and resilience-building strategies within local communities. Subjects and Methods: This study employed a quantitative research approach using a descriptive survey design. Data were collected from 200 respondents selected through purposive sampling techniques in communities surrounding Lake Limboto. Structured questionnaires using Likert-scale measurements were distributed to assess perceptions regarding adaptive governance, institutional capacity, public participation, flood risk awareness, and community resilience. The collected data were analyzed using descriptive statistical analysis, including frequencies, percentages, mean scores, standard deviations, and reliability testing with SPSS software. Results: The findings indicate that community participation and social capital recorded relatively high mean scores, demonstrating strong public involvement in environmental governance and resilience-building activities. Trust in local institutions was also relatively high, although respondents perceived governance responsiveness and policy implementation as moderate. Stakeholder collaboration between local governments and civil society organizations contributed positively to governance effectiveness, while institutional coordination, resource limitations, and weak policy responsiveness remained major challenges. Adaptive governance also improved institutional capacity, environmental sustainability, and social cooperation within communities. Conclusions: Adaptive governance contributes significantly to strengthening community resilience in Gorontalo through participatory governance, stakeholder collaboration, and institutional development. However, improving policy responsiveness, institutional coordination, and sustainable environmental management remains essential to enhance long-term resilience and governance sustainability.